Maternal aggression and child temperament in families with ARFID children in Indonesia - Prasetyo, Yoyok Bekti; Wahyuni, Fitri; Nursalam, Nursalam; Hargono, Rachmat; Ahsan, Ahsan; Melliza, Nur (Aṭfālunā Journal of Islamic Early Childhood Education, 2023)
Aggressive behavior in parenting is a crucial factor for the temperament of children. This study evaluated the relationship between the mother's aggressive behaviors and her children's temperament. The research design applied a cross-sectional survey by using multistage sampling. Two hundred forty-five participants joined this study by responding to a questionnaire. Good aggressive behaviors from caregivers to protect children against physical and psychological harm and danger were observed in mothers aged 26-35 (89.9%) and well-educated mothers (96.8%). The data showed that 4.54 (± 0.912) mothers protect their children from unhealthy foods. The temperament of children was not related to age (p-value = 0.372), mothers' educational background (p = 0.824), and mothers' job status (p = 0.705). Family income had no relation with the child's temperament (p-value = 0.253). There was no relationship between mothers' aggressive behaviors and the temperament of children in avoidant restrictive food intake disorder (ARFID) child cases. The number of children and the aggressive behavior from the mother affected the child's temperament. This study contributes insight into the interplay between a mother's aggressive behaviors and her children's temperament. Subsequent research could delve deeper into specific factors influencing children's temperament in the ARFID case.